Thalictrum daguanense (Ranunculaceae) is merged with T. omeiense, a species distributed in Sichuan and Yunnan, China - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Thalictrum daguanense, described from Daguan county in northeastern Yunnan, China, is conspecific with T. omeiense, a species distributed in southwestern and southeastern Sichuan and northeastern Yunnan. We therefore reduce T. daguanense to the synonymy of T. omeiense herein.